2016
DOI: 10.3389/fmicb.2016.01788
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulation of Rhizosphere Bacterial Communities by Application of Bio-organic Fertilizer in Pseudostellaria heterophylla Monoculture Regime

Abstract: The biomass and quality of Pseudostellariae heterophylla suffers a significant decline under monoculture. Since rhizosphere miobiome plays crucial roles in soil health, deep pyrosequencing combined with qPCR was applied to characterize the composition and structure of soil bacterial community under monoculture and different amendments. The results showed compared with the 1st-year planted (FP), 2nd-year monoculture of P. heterophylla (SP) led to a significant decline in yield and resulted in a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…In this study, the relative abundance of Burkholderia , Nitrospira , and Streptomycetales was significantly higher with organic fertilizer treatment. Previous studies have found that Burkholderia was able to inhibit the growth of pathogens and in effect acted as a Bio-organic fertilizer to improve plant growth [49–50]. Nitrospira is a ubiquitous bacterium that has a role in the nitrogen cycle by performing nitrite oxidation in the second step of nitrification [5152].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the relative abundance of Burkholderia , Nitrospira , and Streptomycetales was significantly higher with organic fertilizer treatment. Previous studies have found that Burkholderia was able to inhibit the growth of pathogens and in effect acted as a Bio-organic fertilizer to improve plant growth [49–50]. Nitrospira is a ubiquitous bacterium that has a role in the nitrogen cycle by performing nitrite oxidation in the second step of nitrification [5152].…”
Section: Discussionmentioning
confidence: 99%
“…We found similar results that the soil of a non-fertilized paddy field had high N fixation activity, which could promote rice growth, and diversified the N-fixing microorganisms significantly as compared to fertilized soil [46]. Microbial diversity in a plant’s rhizosphere is known to play various beneficial roles by degrading different organic substances and uplifting plant health, by playing antagonistically against harmful microbial communities [22]. According to our bacterial functional analysis there was a higher abundance of bacteria that play a role in the health of plants and soil in RC under LN.…”
Section: Discussionmentioning
confidence: 88%
“…Another cardinal aspect to improve plant growth and yield involves studying the plant rhizospheric compartments, including rhizosphere soil (loosely attached soil to root), rhizoplane (soil surrounding the root surface), and endosphere (inside of the root). The process within plant roots, such as nutrient uptake, respiration, and root exudation, can significantly affect the chemical properties of rhizosphere soil and orchestrates the community structure of rhizosphere microorganisms [22].…”
Section: Introductionmentioning
confidence: 99%
“…( Wu et al, 2017 ). The depletion in soil nutrients ( Bennett et al, 2012 ), the autointoxication of root exudations ( Araya et al, 2012 ), and the imbalance of rhizospheric microflora ( Wu et al, 2016a ) are thought to be the main reasons for CMP. Increasing the amount of chemical fertilizer does not alleviate this problem ( Wardle et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%